The p53/RMRP/miR122 signaling loop promotes epithelial-mesenchymal transition during the development of silica-induced lung fibrosis by activating the notch pathway. (January 2021) - Huang, Ruixue; Bai, Chenjun; Liu, Xiaodan; Zhou, Yao; Hu, Sai; Li, Decheng; Xiang, Jing; Chen, Jihua; Zhou, Pingkun
Abstract: Background: Understanding the roles of long noncoding RNAs (lncRNAs) in EMT would help with establishing novel avenues for further uncovering the mechanisms of lung fibrosis and identifying preventative and therapeutic targets. This study aimed to identify silica-induced specific lncRNAs and investigate the feedback loop regulation among their upstream and downstream genes. Methods and materials: A microarray assay, quantitative real-time polymerase chain reaction and Western blot analysis dual-luciferase reporter gene activity and chromatin immunoprecipitation assays were used. Moreover, a silica-induced lung fibrosis mouse model was used to verify the roles of the lncRNAs. Results: Following silica exposure, both RNA component of mitochondrial RNA processing endoribonuclease (RMRP) and p53 were significantly upregulated during the EMT. The upregulation of p53 upon silica exposure activated RMRP expression, which promoted the EMT. When RMRP is overexpressed, additional RMRP acts as a sponge to bind to miR122, thus decreasing miR122 levels. Using microarrays, miR122 was identified as a potential upstream regulator of p53. This relationship was also verified using the dual-luciferase reporter gene. Hence, decreased miR122 levels result in an increase in p53 activity. More importantly, RMRP promotes the transcription of Notch 1, which, in turn, results in Notch pathway activation. We show that the p53/RMRP/miR122 pathway creates a positive feedback loop that promotes EMT progress by activating the Notch signaling pathway. Conclusion: Our data indicated that p53/RMRP/miR122 feedback loop might contribute to the EMT development by activating Notch pathway, which provides new sight into understanding of the complex network regulating silica-induced lung fibrosis. Highlights: Environmental silica exposure activates p53 to create a positive feedback loop that promotes EMT progress. Notch pathway was activated by RMRP. This study provides new sight into understanding of the complex network regulating silica-induced lung fibrosis.